Capitalismo estatal o convergencias populares - Sara Latorre; Alejandra Santillana (Íconos, 2009)
Este artículo analiza las interacciones entre el gobierno actual y el movimiento anti-minero para el periodo 2006-2009, bajo la hipótesis de que el modelo neo-desarrollista adoptado por el primero ha generado un nuevo escenario de conflictividad social, donde la correlación de fuerzas está signada por la abrumadora popularidad del gobierno, por un lado y por el otro, por los problemas de organización, direccionalidad y estrategias que han dificultado la consolidación y fortaleza del movimiento anti-minero.This article analyses the interactions between the current government and the anti-mining movement between 2006 and 2009. The main hypothesis of the article holds that the neo-developmentalist model adopted by the government has given way to new forms of social conflict. On the one hand, the nature of this social conflict is marked by the overwhelming popularity of the government. On the other hand however, the anti-mining movement has been weakened by problems related to its organisation, leadership and strategies, which have, in turn, prevented its consolidation.